Emerging Modes of Treatment of IgA Nephropathy - Maixnerova, Dita; Tesar, Vladimir (International journal of molecular sciences, 2020)
IgA nephropathy is the most common primary glomerulonephritis with potentially serious outcome leading to end stage renal disease in 30 to 50% of patients within 20 to 30 years. Renal biopsy, which might be associated with risks of complications (bleeding and others), still remains the only reliable diagnostic tool for IgA nephropathy. Therefore, the search for non-invasive diagnostic and prognostic markers for detection of subclinical types of IgA nephropathy, evaluation of disease activity, and assessment of treatment effectiveness, is of utmost importance. In this review, we summarize treatment options for patients with IgA nephropathy including the drugs currently under evaluation in randomized control trials. An early initiation of immunosupressive regimens in patients with IgA nephropathy at risk of progression should result in the slowing down of the progression of renal function to end stage renal disease.
Keywords: klinické zkoušky jako téma; směrnice pro lékařskou praxi jako téma; IgA nefropatie; Practice Guidelines as Topic; ACEI; proteinuria; IgAN; Glomerulonephritis, IGA; CKD; Models, Biological; Clinical Trials as Topic; zvířata; Humans; progression; biologické modely; rizikové faktory; corticosteroids; Risk Factors; lidé; Animals